If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 2) + 4 = 5(x + 3) + 4 Reorder the terms: -3(2 + x) + 4 = 5(x + 3) + 4 (2 * -3 + x * -3) + 4 = 5(x + 3) + 4 (-6 + -3x) + 4 = 5(x + 3) + 4 Reorder the terms: -6 + 4 + -3x = 5(x + 3) + 4 Combine like terms: -6 + 4 = -2 -2 + -3x = 5(x + 3) + 4 Reorder the terms: -2 + -3x = 5(3 + x) + 4 -2 + -3x = (3 * 5 + x * 5) + 4 -2 + -3x = (15 + 5x) + 4 Reorder the terms: -2 + -3x = 15 + 4 + 5x Combine like terms: 15 + 4 = 19 -2 + -3x = 19 + 5x Solving -2 + -3x = 19 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + -3x + -5x = 19 + 5x + -5x Combine like terms: -3x + -5x = -8x -2 + -8x = 19 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -8x = 19 + 0 -2 + -8x = 19 Add '2' to each side of the equation. -2 + 2 + -8x = 19 + 2 Combine like terms: -2 + 2 = 0 0 + -8x = 19 + 2 -8x = 19 + 2 Combine like terms: 19 + 2 = 21 -8x = 21 Divide each side by '-8'. x = -2.625 Simplifying x = -2.625
| 3x+7=4x+1 | | 4x+7-x=19 | | 4(k-1)-2(3k+2)+14=0 | | -5=2x-7 | | 6x+5=2x-4 | | 0.6x-0.8(3-x)=6.7 | | 5-2(x+3)=10 | | 1/6(12t+48)-20=-1/8(24t-144) | | 6x-4(9-x)=17 | | 15(x-5)=-7-8 | | -15=-3-6x | | X^3-3x^2-x=0 | | -6+6k=5k | | 8r=-5+9r | | (m-12)(m-12)=225 | | 3t-2=5t-4 | | 54(-1)(5)= | | z^3x+z^2x^2+6z^2x-6zx^2= | | 4v^2-12v+72=0 | | 12=3-3x | | 5X+2X=-7+8X | | 2v=8+v | | 3x+2y=25 | | -7h=-6h+7 | | 3-2x=x+18 | | 10=4+2x | | x(x+8)(x-3)=0 | | 225c^2+256=0 | | bz+dz+bx+dx= | | -1[8+1(-8+1)]+11= | | 2x=3+8 | | 16-x=7 |